PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA TERPADU KELAS VIII SMP IT DARUL IKHLAS AL-ISLAMI - Sry Mulyani; Rivo Yulse Viza; Eko Wulandari (BIOCOLONY, 2023)
The results of Integrated Science learning for Class VIII Boys at SMP IT Darul Ikhlas Al-Islami were only 18.75%, which reached the minimum limit criteria set by the school, namely 74. This was caused by several factors, such as students being lazy to ask the teacher if the subject matter they were learning was do not understand, and lack of enjoyment of reading science learning material from within students. To overcome these problems the researchers tried to apply the Problem Based Learning (PBL) model. This study aims to improve the learning outcomes of class VIII students of SMP IT Darul Ikhlas Al-Islami. This research method is classroom action research (CAR). This research was conducted in 3 cycles, each cycle consisting of 2 face-to-face meetings and 1 evaluation. The results of this class action research can be seen from the average value increasing from 30.51 in cycle I to 52.42 in cycle II, and to 80.62 in cycle III. While seen from the completeness of student learning from 0% in cycle I to 37.5% in cycle II, and to 75% in cycle III.